The diversity of constitutional adjudication and the universality of constitutional justice: common issues and challenges - Mokhtar, Khairil Azmin; Satriawan, Iwan (2018)
Constitutionalism and constitutional justice are inseparable. Constitutional norms in a country embedded in the constitution are normally administered by the constitutional court. The court as the body that adjudicates constitutional matters thus plays important role on realizing constitutionalism and democracy. This paper explores various frameworks of constitutional adjudication employed by countries all over the world. This is a qualitative doctrinal research which uses historical, conceptual, and legal approaches. Initially the paper defines the concept of constitutionalism, constitutional justice and democracy. It also observes grounds for adopting different methods and frameworks of constitutional adjudication in various jurisdictions and examines main models of constitutional adjudication practiced throughout the world. Issues facing constitutional adjudication in various jurisdictions are highlighted. The study found that the emergence of the concept of constitutional adjudication all over the world was the result of spirit to construct a democratic government and provide fundamental rights protection of citizen through judicial review mechanism. In addition to serve the objective constitutional adjudication mechanism also become part of checks and balances mechanism among other organs of government. The common aspiration of all countries is constitutional justice. In spite of the common theme they are differences in formulating the models of constitutional adjudication. There are several models of constitutional adjudications employed by government of different countries, and the choice of models was influenced by the historical and political background of the countries.